Mesalamine-induced myocarditis following diagnosis of Crohn's disease: a case report - Galvão-Braga, C; Martins, J; Arantes, C; Ramos, V; Vieira, C; Salgado, A; Magalhães, S; Correia, A (Sociedade Portuguesa de Cardiologia, 2013)
Mesalamine is a common treatment for Crohn's disease, and can be rarely associated with myocarditis through a mechanism of drug hypersensitivity. We present the case of a 19-year-old male who developed chest pain two weeks after beginning mesalamine therapy. The electrocardiogram showed slight ST-segment elevation with upward concavity in the inferolateral leads; blood tests demonstrated elevated troponin I and the echocardiogram revealed moderately depressed left ventricular systolic function with global hypocontractility. Cardiac magnetic resonance imaging confirmed the diagnosis of myocarditis, revealing multiple areas of subepicardial fibrosis. The onset of symptoms after mesalamine, and improvement of chest pain, cardiac biomarkers and left ventricular systolic function after discontinuing the drug, suggest that our patient suffered from a rare drug-hypersensitivity reaction to mesalamine.
Keywords: Doença de Crohn; Miocardite; Mesalamina